Analysis of profit contribution variance between actual and plan - Sönke Albers (Universität Kiel, Institut für Betriebswirtschaftslehre; ZBW – Leibniz Information Centre for Economics, 1993)
The traditional techniques of calculating quantity and price variances for analyzing deviations of realized profit contribution (actual) from the planned profit contribution only offer the benefit of identifying areas where problems may exist, rather than diagnosing the causes of these problems. Therefore, it is proposed to base profit contribution variance analysis on market response functions which have been assumed when fixing the planned marketing budgets, prices and quantities. This allows for a decomposition of total contribution variance into causal sources such as realization, effectiveness, reaction and planning variance. It is also shown how the variance of any such source can be separated into effects caused by exogenous factors as well as single market instruments.
Keywords: 650; Rentabilität; Kostenrechnung; Marktforschung; Theorie; Marketingmanagement